Kajian Penetapan Cagar Budaya Bangunan SMP Negeri 1 Pekalongan - Vita Marshinta Devi (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2022)
Cultural Conservation is a cultural heritage that is material in nature, which can be in the form of objects, buildings, structures, sites, and Cultural Conservation Areas, both on land and/or in water that need to be preserved because they have important values for history, science, education, religion and/or culture through the determination process. Some objects in Pekalongan City can be categorized as objects that are suspected to be cultural heritage. In order to maintain the existence of these objects, it is necessary to have preservation efforts through the assessment process, which are then designated as Cultural Conservation. One of the areas in Pekalongan City in which there are several objects of cultural heritage is the Jetayu area. One object that is suspected of being a cultural heritage is the SMP Negeri 1 Pekalongan building. In the process of determining to become a Cultural Conservation, it is necessary to study the building of SMP Negeri 1 Pekalongan in accordance with the criteria set out in the Cultural Conservation Act, both in terms of the age of the object (aged 50 years or more), representing the shortest style period of 50 years, has special meaning for history, science, education, religion, and/or culture and has cultural value for strengthening the nation's personality. It is hoped that with this study its existence in the Jetayu area as a city-level cultural heritage building and the function of the building as a means of education to add and strengthen the value of the area as a heritage area. Keywords: Cultural Conservation, Preservation, Study, Cultural Heritage Building.